Model of traditional game-based extracurricular activities for strengthening character education - Suprayitno Suprayitno; Wiryanto Wiryanto; Budiyono Budiyono; M. Gita Primaniarta (Universitas PGRI Madiun, 2023)
School programs with extracurricular development based on traditional games are prepared to change students' habits in their motor skills. Traditional games are fun activities to form children's motor skills and also help improve children's intelligence. The purpose of this study is to explain the model of traditional game extracurricular activities that can improve students' character in terms of their talents and interests. The research method used is thematic qualitative research to thoroughly investigate a program using the Nvivo12 Software. The subjects of this research were the headmaster of the low grade coordinator, the high grade coordinator and the sports subject teacher. The resulting data processing results started from two questions about traditional games and character education to answer 2 themes and 8 sub-themes. The results of the study show that the Sekolahe Arek Suroboyo program based on traditional extracurricular games is implemented to create a safe, recreational, educative and cooperative school environment. Traditional game-based extracurriculars taught to students include egrang, gobak sodor and terompah. The game was chosen because it is a source of developing students' talents that are local wisdom by using basic body movements in children. The extracurricular activity model accommodates all students who choose traditional games from grades 1-6 by arranging a schedule after school hours are finished. The Sekolahe Arek Suroboyo program by implementing traditional games has a nationalist character, cooperation and independence.